Variação craniana, bacular e citogenética em três populações de Thrichomys apereoides (Lund, 1839) (Rodentia: Echimyidae) do nordeste, centro e sudeste do Brasil - Silva, André Luiz Guedes da (2005)
Five nominal forms in Thrichomys has described, but this genera is currently regarded as monotypic. Thrichomys apereoides (Lund, 1839) described from Lagoa Santa (Minas Gerais) can be distinguished from other genera within the Echimyidae by its soft fur and densely-haired tail. Morphometric, karyological and molecular analysis in Thrichomys suggested that genera is politypic. The present study realized morphological (cranial and bacular) and Karyological analysis in three Thrichomys apereoides samples from Minas Gerais (Lagoa Santa, Matozinhos and Santana do Riacho) within specimens Lund ( 1839) collected, Bahia (Morro do Chapéu, Mucugê Palmeiras and Rio de Contas) and Mato Grosso (Barão de Melgaço) attempt to found independent evolutionary units. Qualitative and quantitative cranial analysis shows differences among the samples studied. Cranial traits conditions, Discriminant Functions Analysis and Principal Component Analysis discriminated the samples. The sample from Bahia has fully discriminated a1ong an axis CV 1 and parti11y discriminated along axis CP 1 . Bacular analysis not discriminated the samples. Karyological analysis discriminated the samples: 2n = 28 and FN = 50 from Minas Gerais; 2n = 26 and FN = 48 from Bahia; 2n = 34 and NF = 64 from Mato Grosso. Thrichomys apereoides is the oldest name the sample from Minas Gerais. Thrichomys inermis is the oldest name the sample from Bahia. Thrichomys pachyurus is the oldest name the sample from Mato Grosso.